Determining Relationships Strategic Human Resources Management Practices And Employee Commitment - Septian Hadi Pratama; Try Junanto; Ai Suminar; Isha Milani (OIKONOMIA: Journal of Economics and Management Science, 2023)
Relationship management is a strategy in which an organization maintains an ongoing level of engagement with its audience.Due to high involvement of human resource management (HRM), it has been a challenge for the organization to manage the external turbulence like war or government policy changes.Employee commitment is considered a key factor in achieving organizational goals.Employee commitment is one of the indicators of success in implementing strategic human resource management practices. In addition, organizational commitment is also stated as an antecedent of various indicators of organizational success.The main purpose of the article is to investigate the relationship between strategic HRM (SHRM) practices and employee commitment (EC) The paper is prepared using a literature review method sourced from textbooks and articles containing both concepts and empirical results. Articles obtained from sciencedirect, MDPI and googlescholar. The results are presented in narrative form. The results of this study are in determining the relationship between strategic human resource management practices and employee commitment has a direct impact on employee commitment. Employee commitment also serves to mediate the relationship between important human resource management practices and various indicators of organizational success, including those related to human resource development and sustainable competitive advantage.